ANALYSIS OF METAPHOR AND SIMILE IN THE POEM AL-I'TIRĀF BY ABU NAWAS - Zikrani Khalilah; Sikni Sari Siagian (Jurnal Eduslamic, 2025)
This paper aims to analyze the influence of the use of metaphors and similes on the aesthetics of Abu Nawas' poetry, especially in the poem entitled " Al-I'tirāf ." Metaphors and similes are two important elements in the style of language used by poets to convey meaning and emotion in a deeper and more aesthetic way. This paper uses a qualitative analysis method for research conducted with a literature study approach, where the poems are analyzed based on the use of metaphors and similes found in the text. The results of the study show that metaphors are used to describe abstract concepts such as sin, regret, and hope for forgiveness, while similes are used to simplify the poet's feelings through comparisons that can be understood by the reader. Both contribute significantly to the aesthetics of the poem, both in terms of meaning and the beauty of language, as well as strengthening the spiritual message that Abu Nawas wants to convey.